Preexisting heart disease underlies newly diagnosed atrial fibrillation after acute ischemic stroke - Rizos, Timolaos; Horstmann, Solveig; Dittgen, Felix; Täger, Tobias; Jenetzky, Ekkehart; Heuschmann, Peter; Veltkamp, Roland (Stroke, 2016)
Whether newly diagnosed atrial fibrillation (nAF) after stroke reflects underlying heart disease and represents an increased risk of cardioembolic stroke, or whether it is triggered by neurogenic mechanisms remains uncertain. We investigated, whether cardiovascular risk factors and echocardiographic parameters in patients with nAF are similar to patients with known AF (kAF) and differ from patients without AF.
Gesehen am 30.04.2020